2015
DOI: 10.1002/hep.28105
|View full text |Cite
|
Sign up to set email alerts
|

A frequent hypofunctional IRAK2 variant is associated with reduced spontaneous hepatitis C virus clearance

Abstract: Patients carrying very rare loss‐of‐function mutations in interleukin‐1 receptor–associated kinase 4 (IRAK4), a critical signaling mediator in Toll‐like receptor signaling, are severely immunodeficient, highlighting the paramount role of IRAK kinases in innate immunity. We discovered a comparatively frequent coding variant of the enigmatic human IRAK2, L392V (rs3844283), which is found homozygously in ∼15% of Caucasians, to be associated with a reduced ability to induce interferon‐alpha in primary human plasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 57 publications
0
17
0
Order By: Relevance
“…ASC, NLRP3 and BTK coding sequences in pENTR clones were generated as described in ( 18) . Truncated Flag-tagged NLRP3 constructs were a kind gift of F. Martinon, Lausanne, Switzerland ( 15) .…”
Section: Methodsmentioning
confidence: 99%
“…ASC, NLRP3 and BTK coding sequences in pENTR clones were generated as described in ( 18) . Truncated Flag-tagged NLRP3 constructs were a kind gift of F. Martinon, Lausanne, Switzerland ( 15) .…”
Section: Methodsmentioning
confidence: 99%
“…ASC, NLRP3, and BTK coding sequences in pENTR clones were generated, as described by Wang et al 18 and in the Methods section in this article's Online Repository.…”
Section: Plasmid Constructsmentioning
confidence: 99%
“…mRNA was isolated with the RNeasy Mini Kit on a Qiacube robot (both from Qiagen, Hilden, Germany) and transcribed to cDNA (High Capacity RNA-to-cDNA Kit; Life Technologies), and Il1b, Nlrp3, IL1B, and NLRP3 mRNA expression was quantified in triplicates relative to TATAA-box binding protein (Tbp/TBP) by using TaqMan primers (Life Technologies) on a realtime cycler (7500 fast; Applied Biosystems, Foster City, Calif), as described by Wang et al 18 Comparable cycle threshold values for TBP (data not shown) in all treatment groups confirmed equal cell numbers.…”
Section: Quantitative Rt-pcrmentioning
confidence: 99%
“…Thus, NIK, a central regulatory kinase for IKK-␣ activation, plays an important role in the IKK-␣-mediated effects on HCV assembly and lipogenic induction. Interestingly, in a recent signalome-wide study, the canonical NF-B pathway was found to restrict HCV infection, while silencing of IRAK2 or NIK of the noncanonical NF-B pathway reduced viral replication (25), thus supporting a proviral role of NIK in HCV infection.…”
Section: Discussionmentioning
confidence: 96%